Narrowband focusing retroreflector with a thin-film structure. (8th July 2021) - Inoue, Junichi; Kusuura, Toshiki; Ueda, Ryohei; Kintaka, Kenji; Ura, Shogo
Abstract: A thin-film narrowband retroreflector is proposed for a diverging free-space wave. The retroreflector consists of a focusing grating coupler in a waveguide resonator on a reflective substrate. The retroreflector is designed and fabricated for an incident wave diverging from a 5.25  μ m diameter spot. The retroreflector gives a reflection towards the divergence point of the incident wave at the resonance wavelength determined by the waveguide resonator, but otherwise a specular reflection. The retroreflection spectrum of a 4 nm bandwidth with the peak of 75% is demonstrated. This configuration will provide a lens-less external-cavity-mirror diode laser of a lasing wavelength fixed to the resonance wavelength.